Pengaruh Pengetahuan, Sikap, Persepsi Terhadap Awareness Labelisasi Farmasi Halal dikalangan Mahasiswa - Cupian; Noven, Sarah Annisa; Anindya, Anindya; Syifa, Anisa; Yudistira, Yudistira (Salam (Islamic Economics Journal), 2025)
The halal status of goods consumed is important for people who embrace Islam. This is a necessity that has been explained in the Qur'an. In this study, consumption was related to the use of halal drugs or halal pharmaceuticals. In Indonesia, the use of halal pharmaceuticals is still minimal due to difficulties in procuring raw materials for halal pharmacy itself plus not all types of pharmaceutical products that have used halal raw materials have been labeled halal. This makes it more difficult for Muslims who want to take halal medicines,  even though Indonesia has the largest Muslim population in the world. This study aims to determine the effect of the level of knowledge, attitudes, and perceptions of Padjadjaran University health students towards awareness of halal pharmaceutical labeling. This study uses a descriptive quantitative approach and the method of data collection using the Random Sampling technique by distributing questionnaires to respondents. The results of data analysis show that the awareness of halal pharmaceuticals labeling is significantly and positively influenced by the variables of knowledge and perception while for the attitude variable has a positive but not significant effect.